Genetic value pollenizer lines of the sugar beet (Beta vulgaris L. ssp. vulgaris var. altissima Doell). - А. О. Яценко; А. І. Опалко; Д. М. Адаменко; В. В. Поліщук; В. Д. Адаменко (Plant Varieties Studying and Protection)
The features of sugar beet polygerm seed populations were studied. The ways of creation of combinationaluable pollenizers line –– component hybrid on sterile base were improve. The environment conditions had influenced on reaction of different types of genic interactions in specific sets of hybrids. The positive effects of interaction is a part of heterosis effects. It is proved that plasticity and stability effect depend on environment condition where genotype realization occurs.